2020
DOI: 10.1002/sctm.19-0216
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic correction of sickle cell disease-derived induced pluripotent stem cells (iPSCs) confirmed at the protein level through serum-free iPS-sac/erythroid differentiation

Abstract: New technologies of induced pluripotent stem cells (iPSCs) and genome editing have emerged, allowing for the development of autologous transfusion therapies. We previously demonstrated definitive β-globin production from human embryonic stem cell (hESC)-derived erythroid cell generation via hemangioblast-like ES-sacs. In this study, we demonstrated normal β-globin protein production from biallelic corrected sickle cell disease (SCD) iPSCs. We optimized our ES/iPS-sac method for feeder cell-free hESC maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…It has been shown that OP9 feeder cells as a mouse bone marrow stromal cell line may enhance the hematopoietic differentiation of human iPSCs [86]. Also, C3H10T1/2 feeder cells have the capacity to stimulate the hematopoietic differentiation of human iPSCs [38,87]. Increasing in vitro evidence indicates that the cell type of origin and an epigenetic memory for iPSCs may influence on the hematopoietic differentiation of human iPSCs [34,88,89].…”
Section: In Vitro Culture Of Human Ipsc-derived Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that OP9 feeder cells as a mouse bone marrow stromal cell line may enhance the hematopoietic differentiation of human iPSCs [86]. Also, C3H10T1/2 feeder cells have the capacity to stimulate the hematopoietic differentiation of human iPSCs [38,87]. Increasing in vitro evidence indicates that the cell type of origin and an epigenetic memory for iPSCs may influence on the hematopoietic differentiation of human iPSCs [34,88,89].…”
Section: In Vitro Culture Of Human Ipsc-derived Rbcsmentioning
confidence: 99%
“…Various techniques have been developed to generate enucleated RBCs from human iPSCs [31,33,34]. Genome editing and human iPSCs technology has greatly accelerated the use of autologous transfusion therapies [35][36][37][38]. In this review, we focused on the generation of human iPSC-derived erythrocytes to present an overview of the current status and applications of this field.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, RBCs derived from PSCs were reported to enucleate inefficiently and express mostly ε‐globin/γ‐globin with no or negligible levels of adult β‐globin 65,66 . Insights into developmental hematopoiesis and understanding of the regulatory mechanisms of globin switching allowed the derivation of relatively higher levels of β‐globin expressing RBCs from PSCs; however, engraftment has again not been demonstrated 67‐70 . Although the improvement in β‐globin expression assumes successful activation of the definitive third wave‐like HSC generation from PSCs, single‐cell analysis in iPSC‐RBCs revealed that one cell can express all globin types to a certain degree 71 .…”
Section: Hsc Generation From Pscs: Transcription Factors Specify the mentioning
confidence: 99%
“…Previous research from the laboratory of Naoya Uchida (National Institutes of Health, Bethesda, Maryland) established that hematopoietic‐like spherical cells derived from human embryonic stem cell‐derived hemangioblast‐like structures (ES‐sacs) could be differentiated into definitive β‐globin‐expressing erythroid cells for potential exploitation in transfusions 11,12 . The team's new STEM CELLS Translational Medicine article sought to advance this research by exploring the ability of gene‐corrected iPSCs derived from sickle cell patients to form definitive erythroid cells in an analogous manner . Haro‐Mora et al began their approach with the biallelic β‐globin gene correction in sickle cell disease iPSCs through the implementation of an electroporation‐based viral vector‐free method following culture under feeder‐free conditions.…”
Section: Featured Articlesmentioning
confidence: 99%
“…And can we apply what we currently understand to other related diseases? In the first of our Featured Articles published this month in STEM CELLS Translational Medicine , Haro‐Mora et al describe both the gene correction of a sickle cell disease mutation in patient‐derived iPSCs and their differentiation into corrected erythrocytes employing a feeder‐ and serum‐free methodology and the generation of a hemangioblast‐like structure containing hematopoietic‐like spherical cells . In a Related Article published recently in STEM CELLS , Huang et al employed CRISPR/Cas9‐mediated gene editing to correct a sickle cell disease mutation in patient‐derived iPSCs and permit the production of erythrocytes expressing the appropriate globin protein from the corrected allele …”
mentioning
confidence: 99%